PINK1-PTEN axis promotes metastasis and chemoresistance in ovarian cancer via non-canonical pathway - Fang Zheng; Jiamin Zhong; Kelie Chen; Yu Shi; Fang Wang; Shengchao Wang; Song Tang; Xiaoyu Yuan; Zhangjin Shen; Sangsang Tang; Dajing Xia; Yihua Wu; et al. (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Ovarian cancer is commonly associated with a poor prognosis due to metastasis and chemoresistance. PINK1 (PTEN-induced kinase 1) is a serine/threonine kinase that plays a crucial part in regulating various physiological and pathophysiological processes in cancer cells. Methods The ATdb database and "CuratedOvarianData" were used to evaluate the effect of kinases on ovarian cancer survival. The gene expression in ovarian cancer cells was detected by Western blot and quantitative real-time PCR. The effects of gene knockdown or overexpression in vitro were evaluated by wound healing assay, cell transwell assay, immunofluorescence staining, immunohistochemistry, and flow cytometry analysis. Mass spectrometry analysis, protein structure analysis, co-immunoprecipitation assay, nuclear-cytoplasmic separation, and in vitro kinase assay were applied to demonstrate the PINK1-PTEN (phosphatase and tensin homolog) interaction and the effect of this interaction. The metastasis experiments for ovarian cancer xenografts were performed in female BALB/c nude mice. Results PINK1 was strongly associated with a poor prognosis in ovarian cancer patients and promoted metastasis and chemoresistance in ovarian cancer cells. Although the canonical PINK1/PRKN (parkin RBR E3 ubiquitin protein ligase) pathway showed weak effects in ovarian cancer, PINK1 was identified to interact with PTEN and phosphorylate it at Serine179. Remarkably, the phosphorylation of PTEN resulted in the inactivation of the phosphatase activity, leading to an increase in AKT (AKT serine/threonine kinase) activity. Moreover, PINK1-mediated phosphorylation of PTEN impaired the nuclear import of PTEN, thereby enhancing the cancer cells’ ability to resist chemotherapy and metastasize. Conclusions PINK1 interacts with and phosphorylates PTEN at Serine179, resulting in the activation of AKT and the inhibition of PTEN nuclear import. PINK1 promotes ovarian cancer metastasis and chemotherapy resistance through the regulation of PTEN. These findings offer new potential therapeutic targets for ovarian cancer management.